AHNS Series – Do you know your guidelines? Principles of treatment for nasopharyngeal cancer: A review of the National Comprehensive Cancer Network guidelines. Issue 2 (29th November 2016) - Gooi, Zhen; Richmon, Jeremy; Agrawal, Nishant; Blair, Elizabeth; Portugal, Louis; Vokes, Everett; Seiwert, Tanguy; de Souza, Jonas; Saloura, Vassiliki; Haraf, Daniel; Goldenberg, David; Chan, Jason
Abstract: This article is a continuation of the "Do You Know Your Guidelines" series, an initiative of the American Head and Neck Society's Education Committee to increase awareness of current best practices pertaining to head and neck cancer. The National Comprehensive Cancer Network guidelines for the management of nasopharyngeal cancer are reviewed here in a systematic fashion. These guidelines outline the workup, treatment and surveillance of patients with nasopharyngeal cancer. © 2016 Wiley Periodicals, Inc. Head Neck 39: 201–205, 2017